2013
DOI: 10.2341/12-067-c
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Examiner Experience on Clinical Performance of Visual Inspection in Detecting and Assessing the Activity Status of Caries Lesions

Abstract: The methods of caries activity assessment associated with the International Caries Detection and Assessment System have similar performance independent of the examiners' levels of experience. However, assessments based on the clinical features of the lesions are less time consuming. SUMMARYOur hypothesis was that a method of caries activity evaluation based on the clinical features of the lesions would be less time consuming but more influenced by the examiner's experience than the scoring system used in assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
32
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(43 citation statements)
references
References 19 publications
5
32
0
2
Order By: Relevance
“…Though many authors have concluded stating that experience or training of the examiner need not influence the detection power of the visual examination tool, experience gained during training seems to be influencing the diagnostic decisions with ICDAS II. 27,28 Visual and enhanced visual, under magnification achieved comparable values of sensitivity and specificity for both the examiners, in our study. In our study, the ICDAS II behaved as a sensitive diagnostic method for occlusal caries diagnosis in the 0-2 codes, irrespective of the use of magnification.…”
Section: Discussionsupporting
confidence: 52%
“…Though many authors have concluded stating that experience or training of the examiner need not influence the detection power of the visual examination tool, experience gained during training seems to be influencing the diagnostic decisions with ICDAS II. 27,28 Visual and enhanced visual, under magnification achieved comparable values of sensitivity and specificity for both the examiners, in our study. In our study, the ICDAS II behaved as a sensitive diagnostic method for occlusal caries diagnosis in the 0-2 codes, irrespective of the use of magnification.…”
Section: Discussionsupporting
confidence: 52%
“…Additional criteria systems for activity assessment have been investigated to be used in association with the ICDAS (ICDAS Coordinating Committee, 2005;Ekstrand et al, 2007;Braga et al, 2009;Braga et al, 2010;Ferreira-Zandona et al, 2012;Gimenez et al, 2013;Piovesan et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, an objective method could be less influenced by examiner's experience than would visual inspection. 4 Considering that LFpen and QLF (red fluorescence measurement) are methods based on the fluorescence emitted by microorganisms present in the caries lesions, 9,11,15 and since active caries lesions are more infected than inactive ones, 16 this possibility would be plausible. The old version of the LF method used with different drying times had been tested for this purpose previously, 28 but this methodology was not compared with visual inspection.…”
Section: Discussionmentioning
confidence: 99%
“…percentage of green fluorescence loss on the suspicious site compared with green fluorescence from sound tooth tissue; Localized enamel breakdown in opaque or discoloured enamel (without visual signs of dentinal involvement) 4 Underlying dark shadow from dentine Probably active -…”
Section: Fluorescence-based Methodsmentioning
confidence: 99%
See 1 more Smart Citation